Pengaruh ROE, Size, dan DER terhadap Harga Saham pada Perusahaan Publik Kategori Restoran, Hotel, dan Pariwisata - Mora sose Purba; Jamaluddin Jamaluddin; Herlinta Pinem; Desi Roulina Sianipar (Universitas Islam Nahdlatul Ulama Jepara, 2020)
The increase in return on equity, company size and debt to equity ratio is not always followed by an increase in share prices in trading, service and investment companies listed on the Indonesia Stock Exchange for the 2014-2018 period. This study aims to examine and analyze how the effect of return on equity, company size and debt to equity ratio on stock prices in trading, service and investment companies listed on the Indonesia Stock Exchange for the 2014-2018 period. The research method used in this research uses quantitative research methods with descriptive quantitative research that is explanatory. The population used in this study were all trading, service and investment companies listed on the Indonesia Stock Exchange totaling 129 companies with a sample size of 39 companies with purposive sampling technique. The data analysis method used multiple linear regression.